Impact of Exogenous Enzymes in Sorghum- or Wheat-Based Broiler Diets on Nutrient Utilization and Growth Performance - Selle, P.H.; Cadogan, D.J.; Ru, Y.J.; Partridge, G.G. (International Journal of Poultry Science, 2009)
The impact of two enzyme preparations in either sorghum- or wheat-based broiler diets on nutrient utilization and growth performance was determined. One preparation (Enzyme A) combined protease, xylanase and ß-glucanase activities and the second (Enzyme P) contained xylanase activity. Sorghum- or wheat-based starter (1-14 days), grower (15-28) and finisher (29-42) diets without or with either Enzyme A or Enzyme P were offered to broilers from 1-42 days post-hatch. Each of the six dietary treatments was offered to six replicates of six birds per cage. Total excreta collections were completed in the grower and finisher phases to determine the effects of dietary treatments on nutrient utilization as assessed by Apparent Metabolizable Energy (AME), Nitrogen (N) retention and N-corrected AME (AMEn). Both preparations contained similar levels of xylanase activity and enhanced nutrient utilization in wheat-based broiler diets with more pronounced responses in the finisher phase. In this phase, Enzyme A significantly increased AME by 0.98 MJ, N retention by 4.80 percentage units and AMEn by 0.95 MJ/kg. Similarly, Enzyme P increased AME by 1.21 MJ, N retention by 4.25 percentage units and AMEn by 1.24 MJ/kg. In contrast, enzyme inclusions in sorghum-based grower and finisher diets did not influence nutrient utilization and this is reflected in significant treatment interactions (p